Peran Tenaga Kerja, Tingkat Pendidikan dan Belanja Pemerintah Terhadap PDRB di Kota Banjarmasin - Shahifah, Mirna; Chandriyanti, Ika (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2021)
This study discusses the role of labor, education level, and government spending on GRDP in the city of Banjarmasin. This study aims to determine the role of labor, education level, and government spending on GRDP in the City of Banjarmasin. The data used by the author in this study uses secondary data with the type of time series from 2010-2018 obtained through the Central Statistic Agency of the City of Banjarmasin and the Central Statistic Agency of South Kalimantan. The data analysis technique used is multiple linear regression analysis with hypothesis testing using the coefficient of determination and the F-statistic test. The results of the analysis show that labor force, education level, and government spending simultaneously play a significant role in the GRDP in the city of Banjarmasin.